Teknologi Budidaya Buah Naga Pada Kelompok Informasi Masyarakat (KIM) Mekar Karya: Besum, Distrik Namblong, Kabupaten Jayapura - Daniel Ayub Dawan (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2021)
Vegetative multiplication techniques, particularly cuttings, are a cost-effective and efficient means to fulfill the demand for dragon fruit seeds on a large scale. The purpose of this study is to see how cocopeat and cutting length affect the growth of dragon fruit (Hylocereus polyrhizus) plants. This study employed a factorial Randomized Block Design (RAK) with two components, three replications, and twelve combinations. In this study, the criteria measured were the number of shoots (shoots), shoot length (cm), shoot growth time, and shoot growth percentage. The results indicated that administering cocopeat to dragon fruit (Hylocereus polyrhizus) development had a very substantial influence on the number of shoots, shoot length, and shoot growth time at 4, 8, and 12 WAP. Cutting length had a very substantial influence on the number of shoots, shoot length, and shoot growth time of dragon fruit (Hylocereus polyrhizus) at 4, 8, and 12 WAP. Dragon fruit has several nutritional and physiological benefits, as well as religious, aesthetic, and economic purposes. Several forms of dragon fruit (red meat) are also high in antioxidants, which help to prevent cancer. Dragon fruit production, like that of other plants, begins with land preparation, nursery preparation, determining plant spacing, constructing planting holes and climbing poles, watering, fertilizing, pruning, pest and disease management, and harvesting.